A poética da escuta: o olhar do coordenador pedagógico na documentação pedagógica como processo reflexivo na formação do professor - Nielsen, Márcia Ribeiro Ferreira (2020)
This research aimed to understand the poetry of pedagogical documentation in teacher’s professional development, in a reflexive and dialectic process with listening and childhood culture, respecting its rights for decision making on a daily basis. This is a qualitative research with a theoretical foundation that defends the documentation as a methodological process in Early Childhood Education which is intertwined with teacher’ education in everyday life in an aesthetical, ethical and political way. The theoretical foundation is based on the Italian approach from Reggio Emilia in dialog with: Altimir (2010); Corsaro (2011); Edwards, Gandini, Forman (1999); Freire (2017); Hoyuelos (2014); Imbernón (2011); Formosinho-Oliveira (2017); Marcelo Garcia (1999) ; Rinaldi (2016); Placco (2016), Szpunar (2018), Tardif (2010), among others. This research has, as the main target, to propose a pedagogical documentation as part of teacher’s professional development in the school and to reflect about the importance of pedagogical documentation in the routine, in order to enhance children’s learning process, as well as to orient teacher’s decision-making and give learning visibility. Specific objectives: a) to analyze the concepts of pedagogical documentation and its function in the teaching practice; b) to show the importance of the formative use of pedagogical documentation in reflexive sessions with teachers; c) to propose a formative itinerary for the coordinators to initiate the methodological process of pedagogical documentation in order to develop it in Early Childhood Education. This research was performed in a private school in the city of São Paulo, with data collection performed with the semi structured interviews with two school coordinators in the referred school, categorized and analyzed according to the content analysis. It results from this research the reflection about pedagogical documentation in the school and the proposal of a formative itinerary